1997
DOI: 10.1159/000291405
|View full text |Cite
|
Sign up to set email alerts
|

Local Immune Response in Infertile Patients with Minimal Endometriosis

Abstract: Objective: To evaluate the role of local immunity in women with minimal endometriosis. Methods: Uterine endometrium and endometrial implants were obtained simultaneously from 30 infertile women with minimal endometriosis and examined immunohistochemically using antibodies of T cell, B cell, macrophage, Langerhans cell, immunoglobulin (Ig)G and complement (C) 3d. Serum IgG, IgA, IgM, C3, C4, antinuclear antibody and anti-DNA antibody were also examined in 24 of the women. Data from uterine endometrium and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, lower levels of IgG in advanced stage disease suggest that early disease is more immunologically active than later stage disease (Gebel et al, 1993). While concentrations of immunoglobulin types in eutopic or ectopic endometrium were similar between endometriosis patients and controls (Nomiyama et al, 1997), increased concentrations of IgG and IgA in peritoneal fluid were reported in women with the disease (Riccio et al, 2017). Yeol et al (2015) also studied key transcription factors in B-cell function, such as B lymphocyte inducer of maturation program (Blimp-1), involved in cell differentiation, and its antagonist B-cell leukemia lymphoma-6 (Bcl-6) in B cells in peritoneal fluid.…”
Section: B Cells In Ectopic Endometriosismentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, lower levels of IgG in advanced stage disease suggest that early disease is more immunologically active than later stage disease (Gebel et al, 1993). While concentrations of immunoglobulin types in eutopic or ectopic endometrium were similar between endometriosis patients and controls (Nomiyama et al, 1997), increased concentrations of IgG and IgA in peritoneal fluid were reported in women with the disease (Riccio et al, 2017). Yeol et al (2015) also studied key transcription factors in B-cell function, such as B lymphocyte inducer of maturation program (Blimp-1), involved in cell differentiation, and its antagonist B-cell leukemia lymphoma-6 (Bcl-6) in B cells in peritoneal fluid.…”
Section: B Cells In Ectopic Endometriosismentioning
confidence: 92%
“…It is unclear whether the number of B cells in peritoneal fluid or in peripheral blood differs in endometriosis patients compared to controls. An increase (Antsiferova et al, 2005;Badawy et al, 1989;Berbic et al, 2013;Chishima et al, 2000;Gleicher et al, 1987;Hever et al, 2007;Lachapelle et al, 1996;Odukoya et al, 1996a;Odukoya et al, 1996b;Riccio et al, 2017;Scheerer et al, 2016), a decrease (Gagné et al, 2003;Oosterlynck et al, 1993) or no significant differences (Christofolini et al, 2011;Gebel et al, 1993 Nomiyama et al, 1997;Witz et al, 1994;Yeol et al, 2015) in B cell numbers in peritoneal fluid and in the circulation have been reported in patients with endometriosis compared to controls. It is difficult to compare the results of these various studies because samples analysed included ectopic endometriosis lesions, peritoneal fluid (reflecting the peritoneal cavity environment) and blood or serum, where the findings are systemic.…”
Section: B Cells In Ectopic Endometriosismentioning
confidence: 98%
“…It is also recognized as a pelvic inflammatory condition, 4 featuring overexpression of inflammatory genes, the release of proinflammatory cytokines (especially prototypical tumor necrosis factor a [TNF-a] and interleukin 1b [IL-1b]), 5,6 nuclear factor kB activation, [7][8][9] and the infiltration of macrophages and lymphocytes. [10][11][12] Emerging evidence indicates that inflammation also activates the coagulation cascade, and coagulation modulates the inflammatory activity. 13,14 Platelets are now increasingly viewed as inflammatory effector cells involved in the activities across the spectrum from acute inflammation to adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is, first and foremost, a hormonal disease, characterized by the increased local production of estrogens due to molecular aberrations in steroidogenesis [ 5 ]. It is also recognized as a inflammatory condition [ 6 ], featuring overexpression of inflammatory genes, the release of pro-inflammatory cytokines [ 7 , 8 ], the activation of NF-κB [ 9 11 ], and the infiltration of macrophages and lymphocytes [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%